Answer:
The answer to this problem is x = 3 and y = -2.
Explanation:
To solve this problem, we first have to remember how to solve problems using substitution. We first solve one equation completely in terms of another variable. In this case, this has already been done for us - the first equation is in the form y = f(x). Next, we should substitute this "value" or function for y into the other equation. This process is modeled below:
y = -4x + 10
y = -6x + 16
If we substitute, we get:
-4x + 10 = -6x + 16
Now this is a simple one variable equation that we can solve easily. First, we should add 6x to both sides, giving us:
2x + 10 = 16
Then, we should subtract 10 from both sides, yielding:
2x = 6
Finally, we can divide both sides by 2 to get:
x = 3
Now, we must plug in this value for x into one of our original equations (it doesn't matter which one we choose) to solve for the other variable, y.
y = -4x + 10
y = -4(3) + 10
y = -12 + 10
y = -2
Therefore, the answer to this problem is x = 3 and y = -2.
Hope this helps!